Phonoaudiology guidance in the preoperative period in the head and neck tumors - Scheidt, Grasiella Aparecida Nau; Fleig, Raquel; do Nascimento, Iramar Baptistella (International Archives of Otorhinolaryngology, 2013)
Introduction: The habit of smoking and intake of alcoholic drinks can lead to the incidence of malignant tumors in several areas, including the head or neck. Phonoaudiology is an area of oncology that is always seeking to expand its applications in oncological head and neck cases, with intervention in pre- and post-operative periods and in different clinical fields.Aim: To evaluate and describe the impact of phonoaudiology preoperative guidance in patients, specifically smokers and alcohol drinkers, with head and neck cancer.Methods: Series Study. Interviews were conducted by telephone with 40 individuals diagnosed with malignant head and neck tumors. Questionnaires regarding the use of tobacco and alcohol were administered before and after the phonoaudiology preoperative guidance.Results: Among the 40 individuals who received phonoaudiology preoperative guidance, 26 were smokers before the orientation. Of these 26 individuals, 18 (69.24%) abandoned tobacco dependence, 4 (15.38%) did not quit smoking, and 4 (15.38%) quit smoking for a few months before resuming smoking after receiving phonoaudiology preoperative guidance. Regarding alcohol consumption, 31 individuals ingested alcohol before phonoaudiology preoperative guidance. Of these 31 individuals, 17 (54.84%) abandoned alcohol dependence, 8 (25.81%) did not abstain from alcohol consumption, and 6 (19.35%) resumed alcohol consumption after a period of abstinence after receiving phonoaudiology preoperative guidance.Conclusion: Phonoaudiology preoperative orientations are effective in the treatment of head and neck malignant tumors.
Keywords: Neoplasms; Alcoholism; Smoking